Change up - Jeter, Derek, 1974-; Mantell, Paul (Simon & Schuster Books for Young Readers, 2017)
Derek is sure this is the start of a winning season. If all goes according to plan, he'll be the starting shortstop and his team will soar to victory. But Derek soon learns that life doesn't always go as planned.